Lexical density in Children's Storybook - Aswani, Ade; Perangin-angin, Alemina Br.; Aswani, Aprilza (Talenta Publisher, 2023)
The purpose of this study was to examine the lexical density of six children’s stories in order to assess the richness and complexity of language usage in these texts. The study examined the selected stories from a children’s storybook using a qualitative content analysis technique to identify the fraction of content words, such as nouns, verbs, adjectives, and adverbs, that contribute to the total lexical density. To measure the lexical density of the storybooks, the analytical approaches were inspired by Ure (1971) and Halliday (1985). The findings demonstrated varying degrees of lexical density in children's storybooks, providing insights into the variable vocabulary and linguistic complexity used in these writings.